Milk production, milk composition and reproductive performance of cows between two dairy farms in Malaysia - Ali, Amer Ibrahim (2020)
The present study aims at evaluating the factors influencing milk composition, milk production, and reproductive performance of selected cow breeds (Friesian and Jersey cows) in two dairy farms in Malaysia. There is a need to explore ways to improve milk production efficiency in Malaysia, considering the growing demand for milk and milkbased products. Besides, there is also a need to understand the factors influencing milk production. An analysis of previous literature revealed no research was done in a holistic manner encompassing the aspects of milk composition, milk production, and reproductive performance of cows simultaneously and no research was conducted within the Malaysian context. In this regard, the researcher ascertains the need to conduct the study. This study used convenience-sampling method in selecting the dairy farms out of the various farms available in the country. The two farms selected for the study are Taman Pertanian Universiti (TPU) and RedAgri Dairy Farm. The selections of these farms were based on the convenience and feasibility of the researcher to approach the farms to collect the data. The TPU farm was considered for data collection as it breeds Friesian-Sahiwal cows, whereas Redagri Dairy Farm breeds Friesian and Jersey. Each farm was used to collect different data based on the convenience of the researcher and the permission acquired from these farms. This study collected data on lactating cows. The findings showed that there is a significant relationship between breed, parity order and year of calving on calving interval, days open, number of service per conception and days to the first insemination but not on reproductive performance of the cows. There are also associations between the various components within milk composition - blood urea and milk urea, blood protein and milk protein concentration, blood progesterone and milk progesterone. It is recommended that future studies focus on these similar factors in other countries to understand the different ways of cow milk yielding to improve the overall global milk production and cow fertility.